Systemological bases of management consulting - Соловйова, К. О.; Ельчанінов, Д. Б.; Бондаренко, М. Ф. (ITHEA, 2008)
The problem of management consulting for sustainable development organization support is discussed. The problem is formally described by means of systemological terms. The mathematical problem solving is considered. Practical use of the obtained results is outlined.
Keywords: systemology; competitive intelligence; management consulting; sustainable development